Sistem Pakar Diagnosa Penyakit Alergi Pada Anak Dengan Menggunakan Microsoft Visual Basic Net Studi Kasus Klinik Dokter Yunita Siregar - Sri Dewi; Kusmanto Kusmanto; Taufiqqurrahman Nur Siagian (U-NET Jurnal Teknik Informatika, 2021)
Food allergies are health problems that arise as a result of a specific immune response to food. The prevalence of food allergy in children is 6%, while in adults it is 3 - 4%. Food allergy prevention strategies that are not yet optimal are one of the causes of the increasing incidence. Immunopathogenesis in food allergies involves reactions between allergens and antibodies that are mediated by immunoglobulin E, non-immunoglobulin E, or both. The clinical implications of food allergy in adults can affect the gastrointestinal, cutaneous, respiratory, and systemic systems. The gold standard for the diagnosis of food allergy is the oral food challenge. The most appropriate treatment is to avoid trigger factors. Specific and nonspecific therapy against allergens can be given although it is still under debate.